Kinetic study on effect of novel cationic dimeric surfactants for the cleavage of carboxylate ester. (29th May 2013) - Kumar, Birendra; Tikariha, Deepti; Ghosh, Kallol K.; Barbero, Nadia; Quagliotto, Pierluigi
Abstract : Kinetic study has been performed to understand the reactivity of novel cationic gemini surfactants viz. alkanediyl‐α, ω‐bis(hydroxyethylmethylhexadecylammonium bromide) C16 ‐s‐C16 MEA, 2Br − (where s = 4, 6) in the cleavage of p ‐nitrophenyl benzoate (PNPB). Novel cationic gemini C16 ‐s‐C16 MEA, 2Br − surfactants are efficient in promoting PNPB cleavage in presence of butane 2, 3‐dione monoximate and N‐phenylbenzohydroxamate ions. Model calculation revealed that the higher catalytic effect of ethanol moiety of gemini surfactants (C16 H33 N + C2 H4 OH CH3 (CH2 )S N + C2 H4 OH CH3 C16 H33, 2Br −, s = 4, 6) is due to their higher binding capacity toward substrate. This is in line with finding that binding constants for novel series of cationic gemini surfactants are higher than conventional cationic gemini (C16 H33 N + (CH3 )2 (CH2 )S N + (CH3 )2 C16 H33, 2Br −, s = 10, 12), cetyldimethylethanolammonium bromide and zwitterionic surfactants, i.e. Cn H2n+1 N + Me2 (CH2 )3 SO3 − (n = 10; SB3‐10). The fitting of kinetic data was analyzed by the pseudophase model. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Nucleophilic catalysis reactions are presented for the cleavage of carboxylate ester in absence/presence of novel cationic dimeric micellar media. Novel cationic dimeric surfactants are shown efficient environment for the acceleration of the rate of reactions compared to other surfactant systems. The reactivity of micellar‐mediated reactions was explained by considering empirical parameters.